2011
DOI: 10.1177/147323001103900118
|View full text |Cite
|
Sign up to set email alerts
|

Gasless Laparoscopy versus Conventional Laparoscopy in Uterine Myomectomy: A Single-Centre Randomized Trial

Abstract: In a single-centre, randomized trial, gasless laparoscopic myomectomy was compared with conventional laparoscopic myomectomy. The study examined feasibility, safety, reliability and post-operative outcomes. Estimated blood loss, duration of surgery, early post-operative outcomes and length of hospital stay were recorded. Compared with conventional laparoscopic myomectomy, gasless laparoscopy resulted in significantly lower intra-operative blood loss (median 100 ml vs 80 ml, respectively) and duration of surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Thirty nine studies were reviewed for eligibility by scrutinizing full-text articles. Eventually, 12 eligible RCTs [13][14][15][16][17][18][19][20][21][22][23][24] were included in this meta-analysis. The PRISMA flowchart is showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty nine studies were reviewed for eligibility by scrutinizing full-text articles. Eventually, 12 eligible RCTs [13][14][15][16][17][18][19][20][21][22][23][24] were included in this meta-analysis. The PRISMA flowchart is showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 40 to 384 patients. Six studies [13,14,16,[18][19][20] were conducted in Italy and the remaining six RCTs [15,17,[21][22][23][24] were conducted in China. The mean age of included patients varied from 28 to 50 years old, and the follow-up period differed from 1 to more than 12 months.…”
Section: The Characteristics Of Included Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further breakdown of this analysis shows that, in 1990s, with the peak interest in gasless technique, studies reported higher conversion rates for adnexal procedures with smaller sample sizes [ 32 , 33 ]. A myomectomy study by Wang and colleagues in 2011, with a larger sample size, did not report any conversions in either group [ 34 ]. One explanation given by Cravello and colleagues was the location of adnexal organs in obese patients resulting in limited views of the pelvis when using the gasless technique [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to current data, there are no significant differences between conventional and gasless laparoscopy regarding blood loss and hospital stay (5,7). Some authors even reported less intraoperative blood loss and less postoperative drainage volume (17). First data suggest that immune response is less in gasless laparoscopy-assisted surgery when compared with traditional laparoscopy, and the difference may have effects on the post operative recovery (18).There is an economic benefit as hospital charges are lower in gasless laparoscopy (5).…”
Section: Discussionmentioning
confidence: 99%